Teaching Spanish as a Foreign Language (E / LE) in Brazil: understanding of socio-historical constructs - Rocha, Nildiceia Aparecida [UNESP]; Maldonado Barreto, Erika Maritza [UNESP] (Univ Politecnica Valencia, Editorial Upv, 2015)
This communication focuses an educational intervention in the classroom of Spanish as a Foreign Language (E/LE) held at the Universidade Estadual Paulista - UNESP - Campus of Araraquara - Brazil, with the aim of presenting the experience of a practical reflexive project around social and cultural imaginary present a selection of short stories by writers of American literature: Juan Rulfo, Mexico (The Burning Plain, 1953), Gabriel Garcia Marquez in Colombia (Eyes of a blue dog, 1974) and Julio Cortazar in Argentina (House taken and other stories, 2007). Made with juniors of E / LE, intermediate level, as an approach to the ways of representing a culture in the literature and an exercise to address possibilities such materials. In addition, the students created plans of E / LE as the proposal developed, in which cultural issues were discussed. These formed the analysis of the teaching and reflection on being a teacher of Spanish as a Foreign Language.
Keywords: Latin American Literature; Socio-historical constructs; Educational intervention; Spanish as a foreign language